1979
DOI: 10.1002/macp.1979.021800906
|View full text |Cite
|
Sign up to set email alerts
|

Modification au deuxième degré de polymères époxydés, 1. Etude sur molécules modèles des polyalcadiènes

Abstract: The addition of benzoic acid to the oxirane ring ofmodel compounds for epoxidized polymers ofdienes was studied. A convenient reaction rate was observed for temperatures of about 100 "C. It was found that the addition reaction can be catalysed by basic compounds. Kinetic studies showed the influence of solvent nature, of concentration of reagents, of catalysts, and of the epoxide structure. The reactivities of various acids showing particular properties (drugs, UV-absorbers, herbicides) were investigated. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The reactivity of nucleophilic reagents toward epoxidized 1,4‐polyisoprene latexes was studied. The objective was to determine whether the nucleophilic reagents that were shown to be able to add onto the epoxidized units of epoxidized rubbers in solution5–10 could also react with the same polymers in latex conditions. The study was achieved with ENR latexes, but also with ELIR latexes coming from LIR‐700 latex, a synthetic rubber latex prepared by emulsification of a synthesized 1,4‐polyisoprene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of nucleophilic reagents toward epoxidized 1,4‐polyisoprene latexes was studied. The objective was to determine whether the nucleophilic reagents that were shown to be able to add onto the epoxidized units of epoxidized rubbers in solution5–10 could also react with the same polymers in latex conditions. The study was achieved with ENR latexes, but also with ELIR latexes coming from LIR‐700 latex, a synthetic rubber latex prepared by emulsification of a synthesized 1,4‐polyisoprene.…”
Section: Resultsmentioning
confidence: 99%
“…ELIR latexes were considered to be models of ENR latexes. The compositions of modified rubbers obtained in latex medium were determined by comparison with that of the phosphorated rubbers prepared in solvent 5–10. After a preliminary study performed with various nucleophiles to verify their ability to react onto epoxidized rubbers in latex medium, a systematic study was achieved with DBP, which was shown to be very reactive in these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If LNR can be compared to synthetic liquid 1,4-polyisoprene and used in the same field of applications, it may be useful to use LNR as starting product for preparation of specific polymers for highly technical applications through judicious chemical modification. 50 It is the same for ELNR, whose reactivity of the epoxide groups toward carboxylic acids, 51,52 amines, 53,54 phosphoric acid derivatives, 55 and alcohols 56 is well known (Fig. 10).…”
Section: Lnr and Elnr As Starting Products For The Synthesis Of New mentioning
confidence: 86%
“…Ring opening of epoxidized units under neutral and mild conditions generally requires the use of a catalyst. Thus, addition of acids and amines to oxirane rings of epoxidized polyisoprenes is conveniently catalyzed by onium salts,1, 7 Brönsted acids and phenolic acids 3, 8–10. However, no catalyst is used in the case of phosphate acid derivatives which provide acidic protons by self‐dissociation equilibrium 6…”
Section: Introductionmentioning
confidence: 99%